Synthesis and characterization of Cr(III), Fe(III), Co(II), Ni(II), Cu(II) and Zn(II) complexes of 2,12-dimethyl-3-13-di-n-propyl-1,4,11,14-tetraazacycloeicosa-1,3,11,13-tetraene - MALA MATHUR; RAGHU N. PRASAD (Journal of the Serbian Chemical Society, 2002)
Metal complexes of a 20-membered tetraazamacrocycle 2,12-dimethyl-3,13-di-n-propyl-1,4,11,14-tetraazacycloeicosa-1,3,11,13-tetraene (L) of the type [MLX2]X (M = Cr(III), Fe(III); X = NO3) [CoLNO3]NO3, [NiL(NO3)2], [CuL]Cl2 and [ZnLCl2] have been prepared by 2 + 2 cyclocondensation of 2,3-hexanedione with 1,6-diaminohexane in the presence of metal ions as templates. These complexes were characterized by elemental analyses, conductances, IR and electronic spectra and magnetic measurements.